PEMBERDAYAAN DIRI TAHANAN MELALUI KEGIATAN PENYULUHAN DI POLRES METRO JAKARTA UTARA - Maria, Kiki; Dewa, Maiko Lesmana; Marlin, Syamsu; Andayani, Keti (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
In relation to the role and purposes of community service, especially for prisoners held at Jakarta Utara Metro Police, there is an interesting phenomenon of formally holding a Community Service program in the prisoner’s meeting room with the theme “Prisoner’s Empowerment through Outreaching Activities at the Jakarta Utara Metro Police”. This community service was aimed at giving training and empowering the resistance. This opportunity is for detainees appointed to represent other detainees.